Critical Care Management of Traumatic Brain Injury - Bharadwaj, Suparna; Naik, Shweta (Journal of Neuroanaesthesiology and Critical Care, 2019)
Traumatic brain injury (TBI) is a significant public health problem. It is the leading cause of death and disability despite advancements in its prevention and treatment. Treatment of a patient with head injury begins on the site of trauma and continues even during her/his transportation to the trauma care center. Knowledge of secondary brain injuries and timely management of those in the prehospital period can significantly improve the outcome and decrease mortality after TBI. Intensive care management of TBI is guided by Brain Trauma Foundation guidelines (4th edition). Seventy percent of blunt trauma patients will also suffer from some degree of head injury. The management of these extracranial injuries may influence the neurological outcomes. Damage control tactics may improve early mortality (control hemorrhage) and delayed mortality (minimize systemic inflammation and organ failure). Neuromonitoring plays an important role in the management of TBI because it is able to assess multiple aspects of cerebral physiology and guide therapeutic interventions intended to prevent or minimize secondary injury. Bedsides, multimodality monitoring predominantly comprises monitoring modalities for cerebral blood flow, cerebral oxygenation, and cerebral electrical activity. Establishing a reliable prognosis early after injury is notoriously difficult. However, TBI is a much more manageable injury today than it has been in the past, but it remains a major health problem.
Keywords: traumatic brain injury; critical care; polytrauma; multimodality monitoring; prognostication